2001
DOI: 10.1002/jms.120
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin quantification in human plasma by high‐performance liquid chromatography coupled to electrospray tandem mass spectrometry. Application to bioequivalence study

Abstract: A rapid, sensitive and specific analytical method was developed and validated to quantify gabapentin in human plasma using acetaminophen as an internal standard. The method employs a single plasma protein precipitation. The analytes are chromatographed on a C4 reversed-phase chromatographic column and analyzed by mass spectrometry in the multiple reaction monitoring (MRM) mode. The method has a chromatographic run time of 4 min and a linear calibration curve over the range 50-10 000 ng x ml(-1) (r > 0.999). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 17 publications
(14 reference statements)
0
35
0
1
Order By: Relevance
“…Because the inherent selectivity of MS/MS method was beneficial in developing a selective and sensitive analytical methodology for trace-mixture analysis (Jemal, 2000), it was necessary to use MS/MS detection for GB level in plasma below the reported lowest LLOQ (40 ng/mL; Ramakrishna et al, 2006;Ifa et al, 2001;Ji et al, 2006). The molecular structures of GB and IS are shown in Fig.…”
Section: Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the inherent selectivity of MS/MS method was beneficial in developing a selective and sensitive analytical methodology for trace-mixture analysis (Jemal, 2000), it was necessary to use MS/MS detection for GB level in plasma below the reported lowest LLOQ (40 ng/mL; Ramakrishna et al, 2006;Ifa et al, 2001;Ji et al, 2006). The molecular structures of GB and IS are shown in Fig.…”
Section: Separationmentioning
confidence: 99%
“…However, most of these methods need to complicated sample preparation such as derivatization, protein precipitation or solid-phase extraction, and are thus laborious and time-comsuming. Recently, sensitive methods for GB determination in serum using GC/tandem mass spectrometry (MS/MS) (Gambelunghe et al, 2005) or LC-MS/MS (Ramakrishna et al, 2006;Ifa et al, 2001;Ji et al, 2006) based on protein precipitation without a derivatization step have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The method most commonly used for GBP quantification in blood or serum is reversed-phase HPLC with derivatization and fluorometric detection [146][147][148]. GC methods have also been reported [149], and more recently, more sensitive and validated LC procedures with MS or MS/MS methods for both clinical and experimental monitoring of GBP in human and animal have been also been described [149][150][151][152][153].…”
Section: Gabapentin (Gbp)mentioning
confidence: 99%
“…Its action is attributed to the irreversible inhibition of the enzyme GABA-transaminase, thus preventing the physiological degradation of GABA in the brain (Ouellet et al 2001). Analytical methods reported for its determination consist of high-performance liquid chromatography (HPLC) (Jiang & Li 1999;Tang et al 1999;Chollet et al 2000;Ifa et al 2001;Ratnaraj & Patsalos 1998;Wad & Kramer 1998), spectrofluorimetry (Belal et al 2002;Hassan et al 2001), gas chromatography-mass spectrometry (GC-MS) (Kushnir et al 1999;Van Lentea & Gatautis 1998), capillary electrophoresis (Rada et al 1998) and spectrophotometry applying Hantzsch reaction (al-Zehouri et al 2001). So far, no traces of any attempts have been found for determination of gabapentin by colorimetric method and the literature is still starving for such analytical procedures.…”
Section: Introductionmentioning
confidence: 99%